Group-based educational inequalities in India: Have major education policy interventions been effective?. (March 2020) - Varughese, Aswathy Rachel; Bairagya, Indrajit
Highlights: India's educational attainment appears to be slow when compared globally. Even after seven decades of policy interventions educational inequality by gender, palce of residents and social groups has been persistant The prevalence of these gaps varies across Indian states. Despite constant policy initiatives, socio-economic factors leave a strong influence on educational attainment and its prevailing inequalities. At the Central government level, Hindu SC, Hindu ST, Muslim population as well as rural females still requires a policy push to overcome these inherent problems from the viewpoint of equalizing educational opportunities. Our findingds also suggest, it's time to give improved focus on secondary and higher education while continuing the efforts on primary education as part of enhancing the overall participation rate. Abstract: Despite seven decades of policy thrust, group-based educational inequalities persist in India. The tenacious social group-based stratification often proves to be a hurdle for educational participation policies to be effectively rolled out. Given these realities, this study reviews all major national education policy interventions since t 1950s. Using four rounds of National Sample Survey (NSS) data, we analysed the pattern of educational attainments in terms of Average Years of Schooling (AYS) and educational inequalities in India for the period 1994-2012. Three indices of inequality - Gini, Theil's enttropy and Atkinson - have been constructed to study inequality by gender, place of residence and social groups. . We also empirically estimated the determinants of educational attainments in India by using OLS and Tobit Models. Further using the Oaxaca-Blinder Decomposition technique, we analysed the educational attainment gaps between groups. The study concludes that policy interventions have done little to reduce the group-based educational attainment gap and it's time to place improved focus on secondary and higher education while continuing the efforts in primary education.